REPRESENTASI BUDAYA PATRIARKI DALAM FILM "SKATER GIRL" (ANALISIS SEMIOTIKA ROLAND BARTHES) - Verawindah (2022)
The film "Skater Girl" is a 2021 film with the theme of social issues in society, namely patriarchal culture. The purpose of this study was to determine the existence of patriarchal cultural representations in the film "Skater Girl" as well as in everyday life. The theory used to explain this research is Roland Barthes' semiotic analysis theory which will produce an analysis of denotative meaning, connotative meaning, and myth. In this study, researchers describe how the representation of patriarchal culture in the film "Skater Girl" which airs on the Netflix platform. This study uses descriptive type analysis, namely screen captures, in the form of images of cut scenes and dialogues that describe patriarchal culture in films. Interviews with informants who have Indian ancestry were conducted as a complementary source of research data. The research analysis was carried out using patriarchal ideology as a research reference. The results obtained are related to the representation of patriarchal culture in the film "Skater Girl" that there is a stereotype category between men and women, job differentiation between men in the public sector and women in the domestic sector, as well as superior status for men and women. inferior to women. Keywords: Representation, Film, Semiotic Analysis Roland Barthes.